A new species group defined in Lycocerus Gorham (Coleoptera, Cantharidae), with description of a new species from Xizang, China. Issue 1 (31st December 2022) - Xi, H. C.; Wang, Y. N.; Yang, X. K.; Liu, H. Y.; Yang, Y. X.
Abstract: The Lycocerus varipubens species-group is defined to accommodate three previously described species and a new species from the Himalayan area, including L. varipubens, L. semiextensus, L. purpurascens comb. nov. & stat. reinst. and L. zayuensis sp. nov. L. purpurascens, originally described in Cantharis and first combined in Lycocerus here, is reinstated as a valid specific name to replace L. rubrispinis syn. nov., which is a replacement name for Cantharis rubripennis . Meanwhile, L. rubrispinis becomes a junior synonym of L. purpurascens. L. varipubens species-group could be distinguished from all other groups by the combination of following characters, the filiform antennae, pronotum wider than long, reddish-brown elytra with weakly or moderately developed longitudinal costae, all pro- and meso-outer claws each with a digtiform tooth in both sexes, and spermatheca with three spiral tubes. The species descriptions are provided with habitus photos, aedeagi, abdominal sternites VIII and reproductive systems of female. L. purpurascens and L. varipubens are recorded to China for the first time. In addition, a morphological phylogenetic analysis shows that the L. varipubens group is sister to L. purpureus group. A distribution map and a key to the species of this species-group are also provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:7C82B6E4-9A71-4893-AD97-5692839D2236